UPAYA PENINGKATAN PEMAHAMAN MEMBACA SISWA KELAS XII IPA 1 SMAN 1 PASAMAN DALAM TEKS DISCUSSION MELALUI TEKHNIK BERDEBAT - Haswinda Abdi (STKIP Pesisir Selatan, 2017)
Abstract Based on the assessment of learning outcomes in the English lesson about reading reading text that genre